Act of treason - Flynn, Vince 1966-2013; Copyright Paperback Collection (Library of Congress) (New York ATRIA Books, 2006)
When a presidential candidate wins the election through sympathy votes two weeks after a terrorist attack kills his wife, CIA operative Mitch Rapp investigates dangerous allegations about the attack's hidden agenda, a case that threatens the government's stability.
Keywords: Rapp, Mitch (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Presidential candidates -- Fiction; Attempted assassination -- Fiction; Washington (D.C.) -- Fiction; Suspense fiction; Political fiction; Spy stories